A revision of the genus Lasianthus Jack (Rubiaceae) from Vietnam - Dang, Van-Son; Naiki, Akiyo (Phytotaxa, 2023)
A revision of the genus Lasianthus Jack (Rubiaceae) from Vietnam is here presented. 73 species and four subspecies are recognized, of which three species are described as new to science (L. bachmaensis, L. chii and L. yersinii) and two species are the new record to the flora of the country (L. latifolius and L. viridiramulis). The Vietnamese species are arranged into two sections: sect. Lasianthus and sect. Nudiflorae Hook.f. Eighteen taxa names are reduced to synonymy according to recent studies. Lists of examined specimens, information on the distribution, habitat and ecology, phenology, vernacular names, taxonomic notes and color plates are provided for 77 taxa. Preliminary conservation status assessments are also given for the three species. A key for identifying all Vietnamese Lasianthus species is provided as well.